Frequency Of Congenital Adhesion Bands In Children With Small Bowel Obstruction - Seemab Aamir; Imran, Muhammad; Habibullah; Saeed, Khawar; Rehan, Muhammad (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: To determine the frequency of congenital adhesion bands in children with small bowel obstruction. METHODOLOGY: This study was designed as a Descriptive cross-sectional study. It was carried out from May 1st 2021, to October 31st, 2021 in the department of Pediatric Surgery, MTI, KTH Peshawar. A total of 101 children of both genders with small bowel obstruction were included in the study. After taking detailed history, thorough clinical examinations, and relevant investigations of all the children were done according to the study protocols. Patients were followed till surger,y and perioperative findings were noted. Data analysis was performed using SPSS version 22.0. RESULTS: The age range in this study spans from birth till 14years of age with a mean age of 5.445±3.10 years, a mean height of 39.703±7.22 inches, and a mean weight was 15.079±4.45 Kg. Congenital adhesion band was observed in 45.5% patients. CONCLUSION: Congenital adhesion band should be among the key differential diagnoses while assessing pediatric patients who present with acute abdomen, or signs and symptoms of intestinal obstruction.